The Relationship Between Exercise Intention and Exercise Behavior of Junior School Students: An Analysis of Chain Mediating Effect - Chen, Yue; Yao, Shu-Jun; Ma, Qi-Shuai; Shao, Wei; Liu, Chao; Guo, Ke-Lei (Frontiers in Psychology, 2022)
Objective: This study explores the relationship between exercise intention and exercise behavior, and constructs a chain mediating model through the mediating effect of implementation intention and self-identity. Method：Through stratified cluster sampling method, 1,573 junior school students (with an average age of 13.71 ± 0.891 years) were evaluated by exercise intention scale, implementation intention scale, self-identity scale and physical exercise grade scale. For data analysis，Common Method Deviation Test, Pearson Correlation Analysis and Model 6 in the SPSS macro program compiled by Hayes for chain mediating test were conducted in turn. Results：（1）There is a marked correlation between positive exercise intention and exercise behavior（r=0.345，p＜0.01, and exercise intention has a significant effect on the direct path of exercise behavior (β=0.162, t=12.355, p＜0.01 )；（2）Exercise intention can positively predict implementation intention (β=0.219，t=10.006，p＜0.01 )and self-identity (β=0.160，t=16.159，p＜0.01); implementation intention can significantly and positively predict exercise behavior (β=0.230，t=12.742，p＜0.01)，and self-identity can significantly and positively predict exercise behavior (β=0.273，t=7.911，p＜0.01)；（3）Implementation intention and self-identity play a significant mediating role between exercise intention and exercise behavior. The mediating effect consists of three indirect effects: exercise intention → implementation intention → exercise behavior (the mediating effect value is 0.050), exercise intention → self-identity → exercise behavior (the mediating effect value is 0.044), exercise intention →implementation intention → self-identity → exercise behavior (the mediating effect value is 0.017). Conclusion：（1）Exercise intention can significantly and positively predict exercise behavior；（2）Implementation intention and self-identity exert a significant mediating effect between exercise intention and exercise behavior, including the separate mediating effect of implementation intention and self-identity as well as the chain mediating effect of implementation intention and self-identity.